Law Enforcement for Fraud Offenders on behalf of Banks Through Online According to Islamic Criminal Law - Putra, Rabullah; Dintara Lubis, Syaddan (Dinasti Research, 2024)
This research aims to find out the modus operandi of criminal fraud on behalf of banks through online, to find out law enforcement for fraud perpetrators on behalf of banks through online at the North Sumatra Regional Police, and to find out the review of Islamic criminal law in fraud cases on behalf of banks through online. This research uses a qualitative empirical research strategy in the field of law. Interviews with members of the North Sumatra Regional Police became the main data source, while literature surveys of online journals, papers, and articles related to fraud legislation became secondary data. Data reduction, data presentation, and conclusion drawing are the three stages of qualitative data preparation. Article 378 of the Criminal Code can be used to regulate the crime of online fraud, according to the above study. To strengthen the legal basis, Article 28 paragraph (1) of the ITE Law can be followed. Islamic criminal law, which is based on hadith and the Quran, does not provide clear guidelines on how to deal with internet fraud involving banks. Islamic law includes general principles that should be followed, and their application depends on the interpretation of local scholars or religious authorities. In the case of online fraud on behalf of a bank, which is included in the crime of fraud, it can be subject to ta'zir punishment such as a stern warning, a material fine whose amount is adjusted to the victim's loss, imprisonment, flogging, or also exile from society for a while.